Analisis Optimalisasi Terhadap Saluran Distribusi Komoditas Strategis Sebagai Bagian Dari Upaya Untuk Mengendalikan Laju Inflasi di Provinsi Papua Selatan - Syukron, Nurkholis (Jurnal Administrasi Karya Dharma, 2025)
This study aims to analyze the optimization of distribution channels for strategic commodities as part of efforts to control the inflation rate in South Papua Province. High inflation in this region is often caused by inefficiencies in the distribution of goods, particularly strategic commodities such as rice, sugar, and fuel. The study employs a descriptive-analytical method with both qualitative and quantitative approaches. Data were collected through in-depth interviews with stakeholders, surveys of distribution actors, and secondary data analysis from relevant agencies. The findings reveal that the main challenges in distributing strategic commodities in South Papua Province include inadequate infrastructure, high transportation costs, and lack of coordination among agencies. To address these issues, the study recommends several strategies, including: improving transportation infrastructure, developing a more efficient logistics system, and enhancing coordination between local and central governments. The implementation of these strategies is expected to facilitate the distribution flow of strategic commodities, reduce distribution costs, and ultimately help control the inflation rate in South Papua Province. Thus, this research provides important contributions to inflation control policies and economic development in the region.